(untitled) (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
vermiculite from a local mine was processed for expansion. Thermal and microwave expansion processes were carried out. The advantages and disadvantages of thermal and microwave processing were considered. Complete dehydration was observed during thermal processing. The removal of molecular water from the mineral composition using the microwave method is preferable due to its low energy and time consumption.